Uma estrutura de integração de dados urbanos para as relações entre urbanização e saúde mental - Carneiro, Mauricio Rolim (2021)
The accelerated urbanization process of the 20th century produced urban phenomena such as megacities, slums, peripheries, huge metropolitan areas and sócio-spatial segregations of low-income populations in alarming proportions. Associated with large demographic growth, these phenomena directly and indirectly impact the mental health of urban populations worldwide, causing huge losses and damages to millions of people. This work presents a set of factors by which urban design and the urbanization process impact mental health and a set of urban indicators for Latin American cities, which will be confronted with each other, establishing networks of relationships between ‘urbanization’ and ‘mental health’ for urban populations. Then, an Urban Data Integration Framework is proposed, based on the structure and the concept of ‘Urban Computing’, which can be used as a basis for future computational models of data collection, data management, analysis and data visualization relating urbanization and mental health. The proposed Framework was tested based on open data from the city of Curitiba (Brazil), using publicly available urban and mental health data. The result of the process identified a data gap necessary for any study that intends to relate the domains of urbanization and mental health in Curitiba.